Optimasi Google Suites dan PowerPoint untuk Membuat Bahan Ajar Kreatif pada Mata Pelajaran PAI - Unik Hanifah Salsabila; Anggi Pratiwi (University of Merdeka Malang, 2021)
The training program aims to increase knowledge of digital literacy. It improves skills in the use of digital platforms, especially Google Suites in Islamic Education learning, and increase creativity in making PAI subjects using PowerPoint software for Islamic interns in Yogyakarta City. Several planned activities in implementing the digital platform optimization program for Islamic Education teachers in Islamic boarding schools proposed to address these different problems, namely as follows: socialization of digital literacy requires content. Then Google Suites and PowerPoint optimization training for Islamic Education learning. Training lasts four days, with a total meeting length of approximately 700-800 minutes for each session. The participants were 12 PAI teachers from several Islamic boarding schools in Yogyakarta who randomly chosen. Training begins at Even Semester and the Odd Semester. Several presenters are involved in the training, namely one digital media specialist, two lecturers on educational technology, and two students. The outcomes to be achieved from this training program are: increasing the knowledge and understanding of teachers about the needs of digital literacy. Then enhance the abilities of teachers to use the Google Suites tool. Last, increasing the creativity of teachers to build teaching materials using PowerPoint.DOI: https://doi.org/10.26905/abdimas.v6i1.5060